Can social capital moderate the impact of widowhood on depressive symptoms? A fixed-effects longitudinal analysis. (3rd October 2021) - Nakagomi, Atsushi; Shiba, Koichiro; Kondo, Katsunori; Kawachi, Ichiro
Abstract: Objectives: Widowhood is associated with increased risks of depression in the surviving spouse. We examined whether an increase in individual-level social capital mitigates the adverse impact of widowhood on depressive symptoms. Methods: We used data from the 2013/2016 waves of the Japan Gerontological Evaluation Study of functionally independent adults aged 65 years or older (men: n = 20, 853; women: n =16, 858). Fixed-effects regression was applied to examine the potential buffering effects of changes in social capital on changes in depressive symptoms following widowhood among married people living with their spouse and/or others at baseline. Results: Widowhood had a deleterious impact on depressive symptoms particularly among men who ended up living alone following their spouse's death. Fixed-effects models revealed that an increase in informal socializing and social participation might buffer the effects of spousal bereavement on depressive symptoms among men who became widowed during the first two years of follow-up and ended up living alone. Discussion: An increase in structural social capital may mitigate the impact of spousal bereavement on depressive symptoms. However, the associations vary by gender, living arrangement, and time since widowhood. Intensive efforts should be directed toward connecting the vulnerable group, widowed men living alone, to sources of social capital.